PENGEMBANGAN LKPD IPAS BERBASIS DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK SEKOLAH DASAR - Ovita, Dhea; Larasati, Sattya Dewi; Pramudiyanti, Pramudiyanti; Dewi, Pramita Sylvia (LPPM UM Metro, 2024)
This research aims to develop Discovery Learning-based worksheets to improve students' learning outcomes on Plant Body Parts material in elementary schools. The research subjects were 23 fourth grade students at SDN 3 Kemiling Permai. The type of research used in this research is Research and Development (R&D) with the ADDIE method. The instruments used in this research are validation sheets, learner response questionnaires, and educator response questionnaires. research data in the form of questionnaire results, worksheet feasibility, results of learner and teacher responses which are analysed descriptively qualitatively based on criteria scores. The results showed that Discovery Learning-based worksheets can improve student learning outcomes with an N-Gain of 0.60. Thus it can be concluded that Discovery Learning-based worksheets can improve the learning outcomes of grade IV students on the material of Plant Body Parts.